India China Supply Chain - Danendran, Rahul (2014)
This research report addresses the topic of India China supply chain. This study would be looking at the existing policies among the China India trade and a real life scenario of this trade will be analysed. By conducting this study, the current situation of trades can be put forward and it will give an idea to what extent trade policies are useful when it comes to trading and to what extent the policies aid the bottlenecks faced by a trader.